A land covers classification system for environment assessment in semi-arid regions of Iran - A. Keshtkar; H. Keshtkar (Desert, 2008)
Land degradation is a major danger which restricting different areas of Iran. Systematic description of the environmentfor detection of environmental changes and the human-related causes and responses is essential in land cover changestudy. Use of land cover data allow detection of where certain changes occur, what type of change, as well as how theland is changing. Existing systems for classification of land cover is limited in the storage of the number of classes and isoften internally inconsistent. Therefore, Food and Agriculture Organization of the United Nations (FAO), developed theland cover classification system (LCCS), a comprehensive parametric classification based upon systematic description ofclasses using a set of independent quantifiable diagnostic criteria. With this approach land cover change detectionbecomes possible at the level of conversion of a class, whereas modification within a certain class type becomesimmediately identifiable by a difference in classifier, or through the use of additional classifiers as is shown in a series ofexamples illustrating the application of the approach to primarily vegetated areas. Our study showed this approach ismatch with exist information and dates for land cover mapping in Iran.